CRYPTOCOCCAL ANTIGENEMIA IN HIV/AIDS PATIENTS USING LATERAL FLOW IMMUNOASSAY DETECTION AT Dr. SOETOMO GENERAL HOSPITAL SURABAYA - Widjaja, Sajuni; Triyono, Erwin Astha; Kawilarang, Arthur Pohan; Rohiman, Abu (Indonesian Journal of Tropical and Infectious Disease, 2018)
Cryptococcus  infection in HIV / AIDS patients results in cryptococcal meningitis, a major cause of subacute meningitis  with 100% mortality if not receiving appropriate antifungal therapy. An examination of cryptococcal antigen will provide risk information for patients who will experience cryptococcal meningitis. Better diagnosis in asymptomatic and symptomatic phases of cryptococcosis are key components to reduce morbidity and mortality. This study aims to determine the proportion of cryptococcal antigenemia in HIV / AIDS patients treated at Intermediate Treatment-Infectious Diseases Unit of Dr. Soetomo General Hospital Surabaya. Cryptococcal antigenemia was examined in HIV / AIDS patients with suspected Cryptococcus infection and CD4+ T cell lymphocyte count <200 cell /Î¼l. The examination used a lateral flow assay diagnostic tool, a simple FDA(Food and Drug Administration)-approved immunochromatographic test system for detection of capsular polysccharide antigens of Cryptococcus species complex (Cryptococcus neoformans and Cryptococcus gattii) in blood. This test meets all of the World Health Organization ASSURED criteria (affordable, sensitive, specific, user friendly, rapid/robust, equipment-free, and delivered). Sensitivity and specifiticy of this method from serum are both 100%. There were 3 positive cryptococcal antigenemia from 41 serum HIV / AIDS patients with suspected cryptococcus infection at Intermediate Treatment- Infectious Diseases Unit of Dr. Soetomo General Hospital Surabaya. All of these patients were male aged over 36 years, had CD4+ T cell lymphocytes <100 cell /Î¼l and had never received antiretroviral therapy before. The proportion of cryptococcal antigenemia in HIV / AIDS patients with suspected Cryptococcus infection at Intermediate Treatment-Infectious Diseases Unit of Dr. Soetomo General Hospital Surabaya was 7.32%.